Watson, Freedom Summer - The Savage Season That Made Mississippi Burn And Made America A Democracy - Briley, Ron (Teaching History: A Journal of Methods, 2011)
While conservative commentator Glen Beck asserts that he is intent on restoring the Civil Rights Movement, in Freedom Summer, Bruce Watson reminds readers that the history and legacy of the movement that transformed America in the 1960s is considerably different from contemporary Tea Party politics. Watson, a journalist who has written fine histories of the labor movement and the Sacco-Vanzetti case, records the courageous efforts of college students in 1964 who risked their lives to assure that all citizens were accorded the promise of American life. With apologies to Tom Brokaw and those who battled fascism during the Second World War, an argument certainly can be made for these 1960s youth as "the greatest generation."